Binding of peanut allergen Ara h 2 with Vaccinium fruit polyphenols. (30th June 2019) - Plundrich, Nathalie J.; Cook, Bethany T.; Maleki, Soheila J.; Fourches, Denis; Lila, Mary Ann
Highlights: Polyphenol binding induced Ara h 2 secondary structural changes. Polyphenol interaction with Ara h 2 significantly decreased IgE binding capacity. Procyanidin C1, chlorogenic acid, and benzoic acid appeared to bind to Ara h 2. Abstract: The potential for 42 different polyphenols found in Vaccinium fruits to bind to peanut allergen Ara h 2 and inhibit IgE binding epitopes was investigated using cheminformatics techniques. Out of 12 predicted binders, delphinidin-3-glucoside, cyanidin-3-glucoside, procyanidin C1, and chlorogenic acid were further evaluated in vitro . Circular dichroism, UV–Vis spectroscopy, and immunoblotting determined their capacity to (i) bind to Ara h 2, (ii) induce protein secondary structural changes, and (iii) inhibit IgE binding epitopes. UV–Vis spectroscopy clearly indicated that procyanidin C1 and chlorogenic acid interacted with Ara h 2, and circular dichroism results suggested that interactions with these polyphenols resulted in changes to Ara h 2 secondary structures. Immunoblotting showed that procyanidin C1 and chlorogenic acid bound to Ara h 2 significantly decreased the IgE binding capacity by 37% and 50%, respectively. These results suggest that certain polyphenols can inhibit IgE recognition of Ara h 2 by obstructing linear IgE epitopes.